Determinan Penggunaan Rokok Elektrik (Vape) dan Dampaknya Pada Generasi Z - Fasyha Benitha Ramadanty; Risky Akaputra; Andriyani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The increasing popularity of e-cigarettes has led to health problems, particularly EVALI. This study aims to analyze several factors that encourage the use of e-cigarettes (vape) and their impact. The analysis method used is a literature review and uses journals published in the last 5 years with Google Scholar, and PubMed as a database. The implementation time of the work began from March-April. Determinants of vape use, namely internal factors such as experience, attitude, and personality. External factors include modern lifestyle, friendship, family, and social class. Other disease impacts include cough, chest pain, dyspnea, nausea, gastrointestinal symptoms, fatigue, and fever. It is therefore desirable to increase individual awareness about the dangers of vaping.